Relationship between PLR Value and Severity of Dengue Infection in Pediatric Patients in the Aster Room at RSUD dr. Soebandi Jember - Gianevan, Nicholas Jirezra; Riyanti, Rini; Shodikin, Muhammad Ali; Rachmania, Sheilla; Dewi, Rosita (Journal of Agromedicine and Medical Sciences, 2025)
Dengue infection is a disease caused by dengue virus infection and transmitted by the Aedes mosquito, and is a major health problem in children, especially in developing countries. The Platelet to Lymphocyte Ratio (PLR) is a novel inflammatory biomarker that has recently been frequently studied and plays a role in the assessment of viral infectious diseases, and the use of PLR in viral infectious diseases has previously found greater potential compared with the Neutrophil-Lymphocyte Ratio (NLR). It is hoped that PLR can become a new biomarker for predicting the severity of dengue infection which is suitable for use in developing countries because PLR ​​is a cheap biomarker and is available in all clinical conditions. This research is a correlative analytical observational study using a cross-sectional approach. This research design was carried out by collecting data from children diagnosed with dengue infection as well as data on platelets and lymphocytes on the first day of admission to the hospital. This research uses stratified random sampling. Data were analyzed using Spearman correlation with a confidence level of 99%. The results of Spearman's correlation analysis showed a strong significant relationship with p<0.01 (p=0.000) and a correlation coefficient of -0.753. In conclusion, there is a significant and strong relationship between the Platelet-to-Lymphocy Ratio (PLR) value and the severity of dengue infection in pediatric patients in the Aster ward of RSUD Dr. Soebandi Jember. If the PLR ​​value increases, the severity of dengue infection will be lower or decrease and vice versa. Keywords: PLR; dengue infection; children; platelets; lymphocytes